Implementasi Sertifikasi Kompetensi Kerja Bidang Pariwisata Dalam Upaya Menanggulangi Tingkat Pengangguran - Alyah Padmavati; Evelin Cindy Pradana (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
This research is motivated by the increasing number of domestic and international tourists visiting Indonesia every year, so the need for qualified and trained workers in the tourism sector is increasing. So in maximizing the economic benefits of the tourism sector, it is important to implement work competency certification in the tourism sector. The purpose of this study is expected to provide policy recommendations for the government and tourism industry managers in increasing the effectiveness of the implementation of work competency certification in the tourism sector in order to reduce unemployment in Indonesia. Data analysis is processed in a juridical-normative manner and data presentation uses secondary legal materials. The results show that through the implementation of work competency certification, the tourism sector can offer better and attractive job opportunities for job seekers so that it can be an effective instrument in reducing unemployment and encouraging economic growth.